1986
DOI: 10.1002/j.1939-4640.1986.tb00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Subfertility in Men with Corrected or Uncorrected Varicocele

Abstract: To evaluate whether correction of varicocele improves fertility, pregnancy rates were compared in 115 varicocele patients consulting for infertility and having oligozoospermia, asthenospermia, or teratozoospermia, in any combination, and FSH levels within the normal range. Ninety of these patients had corrected, and 25 had uncorrected varicoceles, respectively. The value of clinical and seminal parameters for predicting the eventuality of pregnancy for varicocele patients was also studied. Although both groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
5

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 15 publications
2
18
0
5
Order By: Relevance
“…As regards pregnancy, the success was similar in both groups. Similar results were also observed later [8], in a larger group of patients with varicocele treated primarily by embolization. Similar to the results of our own study, several authors also observed that varicocele correlation slightly improves the seminal fluid characteristics.…”
Section: Discussionsupporting
confidence: 84%
“…As regards pregnancy, the success was similar in both groups. Similar results were also observed later [8], in a larger group of patients with varicocele treated primarily by embolization. Similar to the results of our own study, several authors also observed that varicocele correlation slightly improves the seminal fluid characteristics.…”
Section: Discussionsupporting
confidence: 84%
“…Despite the encouraging results obtained in the seminal parameters (significantly increased sperm concentration and motility), fertility of the patients treated cannot be guaranteed [18][19][20][21][22][23]; as demonstrated by numerous studies, this depends on several female and male variables related to spermatogenesis and ovulation. Finally, it may be hypothesised that any significant morphological changes of germ cells are only appreciable over longer follow-up periods.…”
Section: Discussione E Conclusionimentioning
confidence: 77%
“…Gli incoraggianti risultati seminali ottenuti (significativo incremento di concentrazione e motilità degli spermatozoi) non ci consentono tuttavia di fare sicure valutazioni circa la fertilità dei pazienti trattati [18][19][20][21][22][23]; essa infatti, così come dimostrato da numerosi studi, dipende da molte variabili maschili e femminili che influenzano la spermatogenesi e l'ovulazione.…”
Section: Discussione E Conclusioniunclassified
“…While some studies support the defective effect of varicocele on sperm concentration, motility and morphology [3,4,16,19] , others suggest that there are no such effects [20][21][22] . However, the effect of varicocelectomy in patients with isolated sperm morphology defects according to Kruger's strict criteria remains unclear.…”
Section: Discussionmentioning
confidence: 99%